The Production of 1, 3-Propanediol by Aqueous Phase Reforming of Glycerol over Nickel Based Catalyst - Muhammad Fauzi, Fateh Hakeem (Universiti Teknologi PETRONAS, 2016)
1,3-Propanediol is a colourless liquid at room conditions and has a huge demand in the textile industry due to its stability, strength, and specialized monomer. As it is conventionally produced by hydrocarbon routes, the production of 1,3- propanediol has been less sustainable due to the fact that hydrocarbon is a nonrenewable resource. Aqueous phase reforming of glycerol has proven to produce 1,3- Propanediol at significant yields by only utilizing common earth metals such as calcium and aluminium oxides. This opens up a new opportunity to explore this process by optimizing catalyst compositions. Thus the objective of this study is to characterize the catalyst used and analyse its performance curve towards the aqueous phase reforming reaction of glycerol. In this research, six Ca-Ni/Al2O3 catalyst of different composition are synthesized through wetness impregnation method and characterized in Field Emission Scanning electron microscope (FESEM) with EDX elemental analysis; which is done to ensure the right species present and to confirm the composition of each catalyst sample.